Edukasi Dan Pemberian Imunisasi Dasar Di Desa Kaya Pangur Kecamatan Pokhisen Kabupaten Aceh Tenggara - Hasanalita Hasanalita (Fakultas Teknik Universitas Cenderawasih, 2023)
Immunization is one of the efforts to prevent the occurrence of infectious diseases and also one of the efforts to reduce child mortality. Therefore immunization efforts need to be continuously increased to achieve a high level of community immunity so that diseases that can be prevented by immunization. This community service was carried out on September 15, 2022 in Kaya Pangur Village, Pokhisen District, Southeast Aceh Regency. The target of this activity is mothers who have babies and toddlers at Posyandu. Participants 28 participants consisting of mothers of babies under five, cadres, and midwives. This counseling activity was carried out in the form of providing material related to the importance of immunization starting from the definition, types and benefits of each immunization, the side effects of each immunization.